RETAINING EMPLOYEES THROUGH ORGANIZATIONAL IDENTITY AND ORGANIZATIONAL CULTURE - Najibullah A. Umpa (International Journal of Application on Economics and Business, 2025)
This descriptive research investigated the different factors including organizational identity and organizational culture that affect the college professors’ turnover intention or their voluntary cessation of membership in their organization. A survey questionnaire by Saavedra (2013) on organizational identity and organizational culture was utilized. The realms of organizational identity were pride in membership, fit and comfort zone. While the domains of organizational culture were bureaucratic, supportive and innovative cultures. Content validity and reliability were performed to test whether the instrument’s content and composition were fitting to measure the problems considered in this study. Respondents were from five colleges in the province of Lanao del Sur, Philippines. Data was gathered through survey questionnaire to explore the level of organizational identity and organizational culture and their relationship with turnover intention using Pearson-r Correlation. The study revealed that respondents come from both public and private colleges. Most are unmarried, childless, and relatively young. The respondents generally demonstrated high levels of organizational identity and organizational culture, and less likely intent to stay in their organizations. The relationship between organizational identity and turnover intention is consistent, having a high organizational identity leads to less likely intent to leave among employees. While, as the level of organizational culture increases the less likely turnover will occur. This study recommends that organizations must analyze, review and develop further programs, policies and plans to improve organizational identity and organizational culture. These will indeed reduce the turnover intention.